Urban Image. Photography and Images Interactive Semi-immersive - Chiarella, Mauro (DISEGNARECON, 2009)
The traditional relation among photographs and drawing relates the study, the representation and the proyectualidad of settings and landscapes of cities, with a history of the urban image and its methods of elaboration. Since the lineal perspectives and the camera obscura of the vedutistas Italian of the 18th century; passing for the cylindrical panorama of the 19th century; the photographic collage of the vanguards of the 20th century and the contemporary resources of the digital photography, a continuity of the urban graphic speech is built oscillating: of the totality to the fragment, of the lineal conical perspective to the digital collage and of the images two-dimensional to the interactive and semi-immersive 3D image. With the potentiality that suggests the use of the digital photography for the relevamiento, study and proyectación of urban fragments an application developed is described partly in a Workshop International of the Universita di Bologna and a proposal of didactic methodology based on the reconstruction vectorial three-dimensional from spherical panorama 360º.